Poverty and patterns of growth - Hasan, Rana; Quibria, M. G. (Muhammad Ghulam); Asian Development Bank. Economics and Research Department (Manila Asian Development Bank, 2002)
With reference to East Asia.
"August 2002."
Includes bibliographical references (pages 8-9)
Also available via the Internet.
Keywords: Poverty -- Economic aspects; Economic development